Multiple regulatory signals in the control region of the Escherichia coli carAB operon. - Bouvier, J (1984)
The first reaction in pyrimidine and arginine biosynthesis in Escherichia coli is catalyzed by a single enzyme, carbamoyl-phosphate synthetase (EC 6.3.5.5), the product of the carAB operon. Expression of this operon is cumulatively repressed by arginine and pyrimidines. The nucleotide sequence of the carAB control region was determined and transcriptional starts were localized. Two adjacent promoters, 70 base pairs apart, appear to be used in vivo, the downstream one overlapping a typical arginine operator. The absence of any attenuation-like sequence excludes such a mechanism for pyrimidine-mediated repression. Various fragments of the carA promoter-proximal region were fused in vitro with the lacZ gene. Results obtained with these fusions indicate that (i) translation of the carA gene can be initiated in vivo without an AUG codon but very likely with an UUG or an AUU codon; (ii) the carAB downstream promoter is repressed by arginine; and (iii) the carAB upstream promoter is repressed by pyrimidines and subject to stringent control. When carried by a multicopy plasmid the carAB control region escapes repression by arginine and pyrimidines. The existence of a pyrimidine repressor, present in limiting amounts in the cell, is therefore postulated.